Odontogenic differentiation potential of human dental pulp cells cultured on a calcium-aluminate enriched chitosan-collagen scaffold - Soares, Diana Gabriela [UNESP]; Rosseto, Hebert Luís; Scheffel, Débora Salles [UNESP]; Basso, Fernanda Gonçalves [UNESP]; Huck, Claudia [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Springer Nature, 2017)
Objective: The study aims to evaluate the odontogenic potential of human dental pulp cells (HDPCs) in contact with an experimental porous chitosan-collagen scaffold (CHC) enriched or not with a mineral phase of calcium-aluminate (CHC-CA). Material and methods: To assess the chemotactic effect of the materials, we placed HDPCs seeded on transwell membranes in intimate contact with the CHC or CHC-CA surface, and the cell migration was monitored for 48 h. Additionally, cells were seeded onto the material surface, and the viability and proliferation were evaluated at several time points. To assess the odontoblastic differentiation, we evaluated ALP activity, DSPP/DMP-1 gene expression, and mineralized matrix deposition. HDPCs cultured onto a polystyrene surface (monolayer) were used as negative control group. Results: The experimental CHC-CA scaffold induced intense migration of HDPCs through transwell membranes, with cells attaching to and spreading on the material surface after 24-h incubation. Also, the HDPCs seeded onto the CHC-CA scaffold were capable of migrating inside it, remaining viable and featuring a proliferative rate more rapid than that of CHC and control groups at 7 and 14 days of cell culture. At long-term culture, cells in the CHC-CA scaffold featured the highest deposition of mineralized matrix and expression of odontoblastic markers (ALP activity and DSPP/DMP-1 gene expression). Conclusions: According to the results, the CHC-CA scaffold is a bioactive and cytocompatible material capable of increasing the odontogenic potential of human pulp cells. Based on analysis of the positive data obtained in this study, one can suggest that the CHC-CA scaffold is an interesting future candidate for the treatment of exposed pulps. Clinical relevance: The experimental scaffold composed by a chitosan-collagen matrix mineralized with calcium aluminate seems to be an interesting candidate for in vivo application as a cell-free approach to dentin tissue engineering, which may open a new perspective for the treatment of exposed pulp tissue.
Keywords: Endodontics; Extracellular matrix; Regenerative medicine; Stem cells; Tissue engineering